2013
DOI: 10.2298/pif1302117m
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo toxicity of several fungicides and Timorex gold biofungicide to Pythuim aphanidermatum

Abstract: SUMMARYA survey of in vitro and in vivo sensitivity of Pythuim aphanidermatum to several commercial fungicides and a biofungicide was undertaken. An isolate of P. aphanidermatum pathogenic to pepper was collected from a naturally infested greenhouse soil from Smederevska Palanka, Serbia. The P. aphanidermatum isolate was sensitive to all tested products. The obtained EC 50 values were as follows: 10.21 mg/l for propamocarb-hydrochloride, 302.65 mg/l for fosetyl-Al, 11.18 mg/l for mancozeb, 1.27 mg/l for mefeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Less sensitive isolates to azoxystrobin were observed in this study in P. ultimum, P. irregulare complex and P. aphanidermatum . P. ultimum originating from lattughino and basil was the least sensitive species to azoxystrobin with EC 50 values three to six times higher with respect to the average EC 50 of the other five Pythium spp.. One isolate of P. aphanidermatum from pepper (Py 11‐15) was somewhat less sensitive to azoxystrobin compared to the other tested isolates within the same species, but isolated from different hosts in previous studies . Less sensitive Pythium isolates were observed also in P. ultimum and P. irregulare complex by Wheeler et al .…”
Section: Discussionmentioning
confidence: 73%
“…Less sensitive isolates to azoxystrobin were observed in this study in P. ultimum, P. irregulare complex and P. aphanidermatum . P. ultimum originating from lattughino and basil was the least sensitive species to azoxystrobin with EC 50 values three to six times higher with respect to the average EC 50 of the other five Pythium spp.. One isolate of P. aphanidermatum from pepper (Py 11‐15) was somewhat less sensitive to azoxystrobin compared to the other tested isolates within the same species, but isolated from different hosts in previous studies . Less sensitive Pythium isolates were observed also in P. ultimum and P. irregulare complex by Wheeler et al .…”
Section: Discussionmentioning
confidence: 73%
“…The concentration of azoxystrobin found to inhibit mycelial growth of P. volutum (EC50) on agar media was 0.052 ppm (Kerns et al, 2009). The EC50 for P. aphanidermatum was 0.05 ppm to azoxystrobin on agar media (Mihajlović et al, 2013). Isolates of P. irregulare and P. ultimum obtained from corn and soybean fields grew well at 10 and 100 ppm of azoxystrobin on agar media (Broders et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Azoxystrobin (methyl (E)-2-{2-[6-(2-cyanophenoxy)pyrimidin-4-yloxy]phenyl}-3-methoxyacrylate) has activity against both R. solani and Pythium spp. (Grichar et al, 2000;Mihajlović et al, 2013;Windels and Brantner, 2005) and is labelled for Pythium pod rot suppression/control and peg and pod rot control of R. solani and Sclerotium rolfsii in peanut in the US (Anonymous, 2013). Uptake of azoxystrobin into leaves is a gradual process with 1 to 3% of the applied material absorbed into a grape leaf within 24 hr of foliar application (Bartlett et al, 2002).…”
mentioning
confidence: 99%
“…Numerous studies have indicated that several established biocontrol agents, including strains from the genera Bacillus, Pseudomonas, Sphingomonas, Stenotrophomonas and Serratia, can suppress vascular or soilborne fungal pathogens (Ramette et al, 2003;Berg et al, 2000;Mavrodi et al, 2012;Mihajlović et al, 2012a;Mihajlović et al, 2012b;Mihajlović et al, 2013a;Mihajlović et al, 2013b;Bhattacharjee & Dey, 2014). Fungi belonging to the genus Trichoderma and bacteria such as Pseudomonas.spp, or Bacillus subtilis, are the most promising biocontrol agents (Bhattacharjee & Dey, 2014).…”
Section: Antagonistic Microorganismsmentioning
confidence: 99%